MODERN GROWTH IN THE DEVELOPMENT OF INNOVATIVE ACTIVITIES, THE HEALTHCARE SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Kurbanov Ikhtiyor Hikmatovich (Modern American Journals, 2025)
The transition to the innovative path of development of the Republic of Uzbekistan implies a significant change in the role and significance of innovation activity and its result — innovation. Innovations are introduced in all spheres of life, from production and management to consumption and the social sphere, the most important of which is healthcare. Health is also an important driver of well-being and economic activity, as it relates to age, lifestyle, social status, learning, and the spread of social connections and interpersonal support. The healthcare system is the most important area of society. Health care management in Uzbekistan is traditionally based on administrative methods, while investing in the health system is based on indicators of resource provision (bed capacity, number of employees, etc.).
Keywords: innovation path, activity, meso-level, end fund, interpersonal support, welfare, economic activity, investment, lifestyle, social status.